The Complex Dynamics of Agricultural Taxation in Developing Countries - Insights from Indonesia - Rio Fernando Alexander; Twee Leony Bintang Yuristine (Asian Journal of Social and Humanities, 2024)
The agricultural sector in Indonesia holds significant importance in the nation's economy, contributing substantially to the Gross Domestic Product (GDP) while facing challenges in tax revenue collection due to the predominance of micro and small-scale players. This paper examines the unique tax approaches in the agricultural sector, considering the complexities of taxation in developing countries. Through a comprehensive literature review, the study explores four key factors influencing tax compliance: economic factors, non-economic factors, tax administration, and perceptions of tax complexity. The research framework incorporates insights from various scholarly sources, including Scopus and Google Scholar, to provide a holistic understanding of agricultural taxation dynamics. The review reveals a nuanced landscape where taxation policies impact market dynamics, welfare outcomes, and historical trends in the agricultural sector. The synthesis highlights the importance of balancing efficiency and equity in tax systems, considering the specific needs of agricultural producers. Furthermore, the study underscores the significance of tax knowledge, effective tax administration, and clear communication in fostering voluntary compliance among farmers. Moreover, the analysis delves into the complexity of tax design, emphasizing the interplay between tax rates, emissions, investment, and perceptions of fairness. The paper identifies opportunities for future research, including exploring regional variations in tax knowledge impact, assessing the effectiveness of tax audit approaches, and examining innovative tax management tools for agricultural enterprises. Overall, the study contributes to understanding agricultural taxation dynamics and provides insights for policymakers seeking to optimize tax policies in developing countries.